Real-Time Recording and Reconstruction of Holograms Integrating Optical and Digital Technology: Registro y Reconstrucción de Hologramas en Tiempo Real Integrando Tecnología Óptica y Digital (BISTUA Revista de la Facultad de Ciencias Básicas, 2024)
The implementation of a Mach-Zehnder interferometer for hologram recording and a coupled 2F optical processor for reconstruction is presented, allowing both processes to be carried out in real-time. Using a hybrid optical-digital system, the experimental setup employs a CMOS2500 camera and an LCR2500 modulator to achieve high-resolution recording and dynamic reconstruction of holographic images. The experimental results demonstrate the system's capability for real-time holography. Fourier hologram results are presented.
Keywords: Holography; Interference; Diffraction; Fourier